Osmanlı Donanması’nda Kömür Kullanımına Genel Bir Bakış (1781-1850) - Burak Kocaoğlu (History Studies, 2025)
During the period when shipbuilding technology was based on wood, charcoal was used extensively as a heat source in the production of the iron parts of the ships. Thanks to its rich forest resources, the Ottoman Empire, which had a great advantage over its contemporary states in the supply of charcoal, continued its construction activities by supplying charcoal without being dependent on foreign sources. However, this advantageous situation of the Ottoman Empire ended with the start of the construction of steamships in the first quarter of the 19th century. Lacking the means to build such ships, which required know-how and economic power during the construction phase, the Ottoman Empire resorted to purchasing steamships, which it saw as a matter of security and prestige. With the purchase of steamships, the coal needed as an energy source was procured from European countries, especially England. In this study, the types of coal used in the Ottoman Navy during the transition from sailboat to steamship and its areas of use, the ways in which coal was procured, the problems encountered during the procurement process and the Ottoman Empire’s approach to the problems are discussed using archival sources.